2005
DOI: 10.1002/mame.200400186
|View full text |Cite
|
Sign up to set email alerts
|

New Motivation for the Depolymerization Products Derived from Poly(Ethylene Terephthalate) (PET) Waste: a Review

Abstract: Summary: Over the last several decades, the process of recycling polymer waste has been attracting the attention of many scientists working on this issue. Polymer recycling is very important for at least two main reasons: firstly, to reduce the ever increasing volumes of polymer waste coming from many sources: from daily life packaging materials and disposables and secondly, to generate value‐added materials from low cost sources by converting them into valuable materials similar, to some extent, to virgin mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
153
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(156 citation statements)
references
References 100 publications
(135 reference statements)
0
153
0
3
Order By: Relevance
“…The monomers or higher oligomers obtained can be used as building blocks to synthesize other polymers with higher economical values. For example, saturated and unsaturated polyesters [10][11][12], polyurethanes [13][14][15], coating materials [16][17][18][19] and additives [20][21][22] have been synthesized from such building blocks in recent years. A large number of reagents have been used for glycolysis of PET such as ethylene glycol [23][24][25][26], diethylene glycol [27,28], propylene glycol [29], neopentyl glycol [14], 1,4-butanediol [30,31], and some synthetic oligoesters [32,33].…”
mentioning
confidence: 99%
“…The monomers or higher oligomers obtained can be used as building blocks to synthesize other polymers with higher economical values. For example, saturated and unsaturated polyesters [10][11][12], polyurethanes [13][14][15], coating materials [16][17][18][19] and additives [20][21][22] have been synthesized from such building blocks in recent years. A large number of reagents have been used for glycolysis of PET such as ethylene glycol [23][24][25][26], diethylene glycol [27,28], propylene glycol [29], neopentyl glycol [14], 1,4-butanediol [30,31], and some synthetic oligoesters [32,33].…”
mentioning
confidence: 99%
“…Since life cycle assessment studies showed that re-utilization of PET has a positive effect on energy balance and the reduction of CO 2 emissions, for ecological reasons, the need of an appropriate PET-recycling is greater than ever [3][4][5][6][7]. Thus, several PET-recycling methods have been developed, which were partially reviewed in the literature [8][9][10][11][12][13][14][15]. One of these methods is the incineration of the PETwaste using the released heat of combustion (direct energy recovery), which amounts to about 46 MJ·kg -1 [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, several PET-recycling methods have been developed, which were partially reviewed in the literature [8][9][10][11][12][13][14][15]. One of these methods is the incineration of the PETwaste using the released heat of combustion (direct energy recovery), which amounts to about 46 MJ·kg -1 [13,14]. Another method, the pyrolysis of the PETwaste is applied to produce a substitute of coal (carbonization) or aromatic and aliphatic compounds as an alternative for fossil fuels (indirect energy recovery).…”
Section: Introductionmentioning
confidence: 99%
“…A introdução da embalagem de PET no Brasil, em 1988, além de trazer as indiscutíveis vantagens ao consumidor, trouxe também o desafio de sua reciclagem. 2 O PET é um dos polímeros mais reciclados em todo o mundo devido à sua extensa gama de aplicações, tais como fibras têxteis, tapetes, carpetes, não-tecidos, embalagens, filmes, fitas, cordas, compostos, e mesmo incinerado para produção de energia. [3][4][5][6] No Brasil, em 2006, alcançamos o segundo lugar na reciclagem do PET, com aproximadamente 51% das embalagens pós-consumo efetivamente recicladas (193,9 mil toneladas das 378 produzidas), perdendo apenas para o Japão, que reciclou 62%.…”
Section: Introductionunclassified
“…Por esta razão, existe uma grande necessidade de reciclagem do PET por dois motivos: ecológico e econômico. 2 O PET é um polímero termoplástico e pode ser fundido e extrudado para produção de fibras, cordas, tubos e mesmo incinerado para produção de energia. 3 A reciclagem química do PET tem atraído a atenção dos químicos devido à grande variedade de processos, resultando em diferentes produtos.…”
Section: Introductionunclassified